THE FINANCIAL FRAMEWORK OF MUSYARAKAH: INSIGHTS FROM BMT BERINGHARJO'S ACCOUNTING PRACTICES - Marwasari, Erni; Fithria, Annisa (IAIN Lhokseumawe, 2024)
Baitul Maal wat Tamwil (BMT), also known as a sharia financial institution, is experiencing a rapid development. As a Microfinance Institution (LKM), BMT operates according to Islamic principles by driving productive economic businesses that promote middle to lower class entrepreneurs, with a focus on independence and self-sufficiency. The aim of this study is to analyze the implementation, determination of profit-sharing ratios, and accounting treatment of revenue from musyarakah-based profit-sharing financing at BMT Beringharjo KC Kauman Yogyakarta, along with its compliance with PSAK 106. This research adopts a qualitative approach with a descriptive method. The data employed in this study comprise both primary and secondary data, collected through interview and documentation techniques. The findings of this study reveal that the profit-sharing ratio is established by distributing profits in a non-proportional manner with respect to the contributed capital, in accordance with the capacity of partners/members. The applied accounting treatment, evaluated based on characteristics, recognition, measurement, presentation, and disclosure, conforms to PSAK 106.